Control integrado de malezas y uso de herbicidas PSI en yuca (Manihot esculenta Crantz) - Piedrahíta Castañeda, Wilson; Mesia P., R.; Doll, J. (1975)
Two studies were conducted to determine the best integrated weed control system for cassava (Manihot esculenta Crantz), in addition to the selectivity of preplant incorporated (PPI) herbicides and their interactions with the planting system. Three preemergence treatments followed by hand weeding or a directed application of paraquat were compared to systems in which the hand weeding was done first and then the preemergence herbicides were directed in cassava 40 days old. Three hand weedings or 3 directed paraquat applications were also included. Best results (highest yields) were obtained when diuron was applied either before or after a hand weeding and when the traditional system of 3 hand weedings was used. The application of a pre-or postemergence herbicide alone was not effective in controlling weeds. Regarding the selectivity of PPI herbicides, EPTC, butylate and trifluralin were applied and incorporated at normal and 2 x rates; the cassava was planted either in ridges or level ground. Butylate was more selective than EPTC. Planting in ridges reduced the selectivity of the thiocarbamates but not of trifluralin, which was selective atthe 2 x rate. Ridging left the area between ridges with less herbicides, thereby reducing weed control. (AS)